SYNTHESIS AND CHEMICAL MODIFICATINON OF NOVOLAC VIAINCORPORATION OF SILICON, PHOSPHOROUS, BORON, SULFUR ANDSOME ORGANIC COMPOUNDS - Pyriadi, Thanun M; Al-Tamimi, Entesar O; Al-Farajy, Ghada H (Al-Nahrain Journal of Science, 2018)
Two types of novolac were prepared, namely / random (o,p-) and (o.o-) novolac. The prepared resins were modified by three methods, the first one includes esterification of phenolic hydroxyl groups in the prepared resins via their treatment with adipoyl chloride and urethane derivative by the reaction of toluene diisocyanate with resins . While the second modification includes incorporation of phosphorous, silicon, and boron into the novolac structure via reaction of P2O5 SiCl2(CH3)2, SiCl2(C6H5)2 and Ba(OH)2 with novolac, Sulfure was incorporated into the novolac structure by preparation of 3,3,5,5 tetra methylo1-4,4-dihydroxy diphenyl sulfone which then reacted with o,o- novolac and the third odification includes reaction of benzyl chloride with sodium salt of novolac and structure contains benzylic ether were obtained. All prepared products were characterized by IR. HNMR, thermal analysis and some physical properties.